2014
DOI: 10.1074/jbc.m114.576058
|View full text |Cite
|
Sign up to set email alerts
|

Adropin Is a Brain Membrane-bound Protein Regulating Physical Activity via the NB-3/Notch Signaling Pathway in Mice

Abstract: Background:The mechanism of action of adropin on metabolism remains elusive. Results: Adropin is a plasma membrane protein that can bind to the brain-specific, non-canonical Notch1 ligand NB-3. Conclusion: Adropin regulates physical activity, motor coordination, and cerebellum development in mice via the NB-3/ Notch1 signaling pathway. Significance: Adropin is a highly conserved polypeptide that might also be important for cerebellum development in mammals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 38 publications
7
107
0
Order By: Relevance
“…Adropin is encoded by the Energy Homeostasis Associated (Enho) gene that is widely expressed in the central nervous system, as well as peripheral tissues such as liver, the heart and skeletal muscles [14][15][16]. While the mechanism of release remains controversial, the rapid regulation according to energy and nutritional status has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Adropin is encoded by the Energy Homeostasis Associated (Enho) gene that is widely expressed in the central nervous system, as well as peripheral tissues such as liver, the heart and skeletal muscles [14][15][16]. While the mechanism of release remains controversial, the rapid regulation according to energy and nutritional status has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the source of the exercise training-induced increase in serum adropin levels remains unclear. Adropin is expressed in vascular endothelial cells, as well as in brain, heart, kidney, liver, pancreas, skeletal muscle, and small intestine (2,32). An in vitro study showed that adropin treatment promotes NO production from the human umbilical vein endothelial cells in a time-dependent manner, mediated via phosphorylation of eNOS protein (20).…”
Section: Discussionmentioning
confidence: 99%
“…Adropin consists of 76 amino acids and is encoded by a gene, Energy Homeostasis Associated (Enho) (16), and expressed in multiple tissues, including the brain, heart, kidney, liver, pancreas, skeletal muscle, and small intestine (2,32). Circulating adropin level decreases with age (7).…”
mentioning
confidence: 99%
“…Whether adropin is actively secreted is controversial, as a recent publication failed to replicate experiments showing secretion of epitope-tagged adropin [18]. However, publications too numerous to be cited here have reported measurements of adropin in the circulation of humans, nonhuman primates, cows, rats and mice.…”
Section: Controversies and Contradictions In The Fieldmentioning
confidence: 96%
“…Another laboratory produced Enho -/-mice [18], and while a similar reduction of physical activity was observed there was no evidence of insulin resistance. Failure to replicate metabolic phenotypes in a mouse models between laboratories is not unprecedented, as genetic background and housing conditions can significantly affect phenotype [24].…”
Section: Controversies and Contradictions In The Fieldmentioning
confidence: 99%